Evaluation of movements of lower limbs in non-professional ballet dancers: hip abduction and flexion - Valenti Erica E; Valenti Vitor E; Ferreira Celso; Vanderlei Luiz Carlos M; Moura Filho Oseas F; de Carvalho Tatiana; Tassi Nadir; Petenusso Marcio; Leone Claudio; Fujiki Edison N; Junior Hugo; de Mello Monteiro Carlos B; et al. (BMC, 2011)
Abstract Background The literature indicated that the majority of professional ballet dancers present static and active dynamic range of motion difference between left and right lower limbs, however, no previous study focused this difference in non-professional ballet dancers. In this study we aimed to evaluate active movements of the hip in non-professional classical dancers. Methods We evaluated 10 non professional ballet dancers (16-23 years old). We measured the active range of motion and flexibility through Well Banks. We compared active range of motion between left and right sides (hip flexion and abduction) and performed correlation between active movements and flexibility. Results There was a small difference between the right and left sides of the hip in relation to the movements of flexion and abduction, which suggest the dominant side of the subjects, however, there was no statistical significance. Bank of Wells test revealed statistical difference only between the 1st and the 3rd measurement. There was no correlation between the movements of the hip (abduction and flexion, right and left sides) with the three test measurements of the bank of Wells. Conclusion There is no imbalance between the sides of the hip with respect to active abduction and flexion movements in non-professional ballet dancers.